Connected domination value in graphs - Angsuman Das (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2021)
In a connected graph G = (V,E), a set D ⊂ V is a connected dominating set if for every vertex v ∈ V D, there exists u ∈ D such that u and v are adjacent, and the subgraph〈D〉induced by D in G is connected. A connected dominating set of minimum cardinality is called a γc-set of G. For each vertex v ∈ V, we define the connected domination value of v to be the number of γc-sets of G to which v belongs. In this paper, we study the properties of connected domination value of a connected graph G and its relation to other parameters of a connected graph. Finally, we compute the connected domination value and number of γc-sets for a few well-known family of graphs.